THE COURSE OF CHICKENPOX IN ADULTS AND CHILDREN - G. A. Kharchenko; O. G. Kimirilova (Детские инфекции (Москва))
The report shows the clinical and epidemiological data analysis of 100 patients with chickenpox adults and children. The comparative frequency of the main symptoms of chickenpox in adults and children, including newborns. The features of the disease in adults: prevalence of severe (70%) with prodromal symptoms, febrile fever, rash abundant large slow and reverse the development of pruritus. We describe the clinical symptoms of chickenpox in infants, depending on the timing of chickenpox disease pregnant women before delivery.  It is noted for heavy chickenpox  in the newborn, the possibility of developing  their generalized forms with the defeat of visceral organs and the central nervous system, diseases of pregnant 3—4 days before delivery. The data on the treatment and prevention tactics doctor for chickenpox.